2005
DOI: 10.1097/01.sla.0000154148.58154.d5
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit in Critically Ill Burned Patients Receiving Selective Decontamination of the Digestive Tract

Abstract: Treatment with SDD reduces mortality and pneumonia incidence in patients with severe burns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(75 citation statements)
references
References 28 publications
0
71
1
3
Order By: Relevance
“…1,2 Although there is still controversy regarding the universal indication of SID for critical care patients, in 5 of 9 published meta-analyses and in 4 recent randomized studies not included in a previous meta-analysis, a reduction in the mortality related to SID administration could be demonstrated in patients admitted to intensive care units (ICUs), mostly when systemic antibiotics were administered. [1][2][3][4][5][6] Bacterial infections (especially those involving gram-negative bacteria) are major complications for liver transplant recipients (LTRs); their frequency ranges from 20% to 80%. They contribute substantially to longer hospital stays and increased hospital costs 7 and are the leading cause of death in this population.…”
mentioning
confidence: 99%
“…1,2 Although there is still controversy regarding the universal indication of SID for critical care patients, in 5 of 9 published meta-analyses and in 4 recent randomized studies not included in a previous meta-analysis, a reduction in the mortality related to SID administration could be demonstrated in patients admitted to intensive care units (ICUs), mostly when systemic antibiotics were administered. [1][2][3][4][5][6] Bacterial infections (especially those involving gram-negative bacteria) are major complications for liver transplant recipients (LTRs); their frequency ranges from 20% to 80%. They contribute substantially to longer hospital stays and increased hospital costs 7 and are the leading cause of death in this population.…”
mentioning
confidence: 99%
“…Afterwards, several randomised studies have found a lower incidence of VAP with SDD [155][156][157][158]; however, a lower mortality rate was not found in some studies [157,158].…”
Section: Pharmacological Measures For Preventing Vapmentioning
confidence: 99%
“…In another study [103], 107 patients with more than 20% burns and/or suspected inhalation injury were randomised to receive SDD or placebo and mortality rates and incidence of pneumonias were measured. A similar antibiotic regimen to the one used in [97] was used but topical polymixin E substituted colistin.…”
Section: The Evidence On Sddmentioning
confidence: 99%